Customer Satisfaction Level Towards Food Delivery Services in Malaysia: A Case Study of Universiti Tun Hussein Onn Malaysia (UTHM), Pagoh - Arwansyah Kirin; Sharifah Khadijah; Mustapha Mustapha; Edriagus Saputra; Muhammad Hafis Hussain (JURNAL KUASA, 2025)
Food delivery service applications have a significant impact on the lifestyle of Malaysians, including students. These applications allow users to order and receive food without having to visit restaurants or food stalls directly. However, some users have expressed dissatisfaction with high delivery fees, unsatisfactory food conditions, and frequent delivery delays. These issues lead to customer dissatisfaction with the services provided. Therefore, this study aims to evaluate customer satisfaction levels with food delivery service applications, particularly among UTHM Pagoh students. The study employs a quantitative methodology with descriptive analysis. Data were collected through an online survey distributed via WhatsApp using the Google Form platform. A total of 300 UTHM Pagoh students participated as respondents in this study. The findings reveal that the majority of customers are satisfied with food delivery services with a mean score of 3.99 categorized as Satisfied. This indicates that food delivery services are quite satisfactory for customers. Nevertheless, all agencies providing food delivery services must improve their facilities to ensure customers can utilize the services without complaints thereby advancing the food service sector in Malaysia. This study contributes to the literature by offering empirical data and contextual analysis that are relevant to consumer behavior in Malaysia and contribute significantly to overall economic growth potency.